PERANAN GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK SISWA DI MTS NURUL HIDAYAH KOTA RAJA KABUPATEN HULU SUNGAI UTARA - Sahidah Sahidah; Ria Susanti; Abdul Wahab Syakhrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research is about the role of the Akidah Akhlak teacher in fostering student morals at MTs Nurul Hidayah Kota Raja, Hulu Sungai Utara Regency. In connection with that, the background of this research is that there are some students when studying they still like to talk to their friends next to them, noisy in class, there are those who like to go in and out of class and there are still some students who speak dirty words. So that the behavior slightly interferes with the learning process. The formulation of the problems studied are: (1) what is the role of the Aqidah Akhlak teacher in fostering student morals. (2) how are the factors that influence in fostering student morals. (3) what is the teacher's strategy of Akidah Akhlak in fostering student morals. The aims of this study were: (1) to find out the role of the Aqidah Akhlak teacher in fostering student morals. (2) to find out the factors that influence the development of student morals. (3) to find out the teacher's strategy Akidah Akhlak in fostering student morals. The subjects in the study were 1 teacher of the Aqidah Akhlak subject at MTs Nurul Hidayah Kota Raja, Hulu Sungai Utara Regency. While the object of this research is about the role of the Akidah Akhlak teacher in fostering student morals at MTs Nurul Hidayah Kota Raja, Hulu Sungai Utara Regency. To obtain the data above, researchers used data collection techniques, namely observation, interviews, and documentaries. Data is processed using data collection, data reduction, data display (data presentation) and data verification (conclusion) techniques. The results of this study found that: (1) the role of the Akidah Akhlak teacher in fostering student morals, namely having the role of the teacher as a guide, the teacher as a motivator, the teacher as a facilitator, the teacher as a learning resource, the teacher as a manager, the teacher as a demonstrator, the teacher as an evaluator, and teacher as a mediator. (2) the factors that influence the development of student morals are internal factors (inside students) which are caused by the nature or habits of students in behavior, while external factors (from outside the student's self), namely from the family environment, social environment or student association . (3) the teacher's strategy in fostering student morals is by fostering and directing students, using a persuasive approach, collaborating with counseling teachers, motivating students, and instilling positive habits.